2013
DOI: 10.1364/oe.21.026198
|View full text |Cite
|
Sign up to set email alerts
|

Vibration frequency measurement using a local multithreshold technique

Abstract: Abstract:In this paper, we demonstrate the use of a video camera for measuring the frequency of small-amplitude vibration movements. The method is based on image acquisition and multilevel thresholding and it only requires a video camera with high enough acquisition rate, not being necessary the use of targets or auxiliary laser beams. Our proposal is accurate and robust. We demonstrate the technique with a pocket camera recording low-resolution videos with AVI-JPEG compression and measuring different objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 12 publications
(11 reference statements)
1
31
0
Order By: Relevance
“…As we stated above, according to what is established in [4], special objects can be tracked with accuracy of the order of 1/N. This affirmation was proved through numerical simulations and with different error criteria.…”
Section: Proposalsupporting
confidence: 66%
See 1 more Smart Citation
“…As we stated above, according to what is established in [4], special objects can be tracked with accuracy of the order of 1/N. This affirmation was proved through numerical simulations and with different error criteria.…”
Section: Proposalsupporting
confidence: 66%
“…In [3], the authors revisited the idea and show that, by using convenient targets, the theoretical maximum accuracy is of the order of 1/N px, being N the total number of pixels in the scene. Although these targets are of difficult implementation, they may be useful to analyze the efficiency of different implementations and even to design new methods [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of accelerometers is sometimes dismissed because of the complexity or accessibility of the specimen to be measured, whereas a laser vibrometer's high cost is still a major drawback in most cases. Thus, computer vision systems [2][3][4][5][6][7][8] have been demonstrated to be a reliable alternative to traditional methods in the last few years. Independently, whether or not they use object recognition, vision-based methods assume that object movement or vibration can be perceived through changes in the light reflected or diffused by a moving target.…”
Section: Introductionmentioning
confidence: 99%
“…After presenting the mathematical basis of the technique [12] and discussing the maximum theoretical subpixel resolution achievable, in [5], the authors demonstrated the possibility of measuring the vibration frequency of objects in a high-speed video sequence simply by counting luminance changes in local regions. The proposal consisted of selecting a local neighborhood or region of interest and applying a multilevel binary threshold to the image within this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation